FORMATION OF SYSTEMICALLY INTEGRATED ACCOUNTING AND THE MECHANISM OF ITS IMPLEMENTATION IN THE SYSTEM OF QUALITY MANAGEMENT OF BUSINESS PROCESSES - S. Ponomareva (Вестник университета)
The study of the issues of the formation of systemically integrated accounting and the mechanism of its implementation in the quality management system of business processes is presented. It is determined that for efficient business management systems not only need to have highly qualified managers and technical base (expensive operating system), but also two information systems that interact on the basis of the principle of convergence and economic viability (growth strategy of the business value) of accounting and analytical control-regulatory system for business management purposes. According to the results of the study, it is concluded that the practical use of this system involves the passage of three stages of action: the choice of basic accounting indicators, transformation, the design of an accounting and analytical and control and regulatory system for business management purposes.